Overview and trend analysis of global hot spring research based on bibliometrics and knowledge graph visualization - Xiaochen Li; Xue Yang; Jibing Ou; Yao Zhou; Lei Xi; Yuzhe Zou; Zihan Chen; Dingwei He; Liqing Yao; Weimo Zhu (Elsevier, 2024)
Background: The scope of hot spring research is continuously growing, with the application of hot spring medicine emerging as a significant trend. However, there is a lack of bibliometric analyses that summarize the current state and trends of the application of hot spring medicine. Objectives: Using bibliometric analysis, this study aims to visualize and analyze the global landscape and emerging trends in hot spring research, focusing on the hotspots and future directions of hot spring medicine application. Methods: Literature from 1994 to 2023 was compiled from the Web of Science Core Collection (WoSCC) database, visualized using Citespace and VOSviewer, analyzing publication trends, keyword co-occurrence, key institutions, and research directions in global hot spring studies. Similarly, literature on the application of hot spring medicine from 2000 to 2024 was also collected. Results: A total of 8020 studies on the global field of hot springs and 68 studies on the application of hot spring medicine met the inclusion criteria. Linear regression reveals significant yearly increases in publication volume (p < 0.001). Five primary research trends including applications, components, diseases, mechanisms, and regions have been identified. Japan and France emerge as the primary contributor to the medical applications of hot springs. Conclusion: Examining utilization patterns, conducting compositional tests, investigating therapeutic mechanisms, and scrutinizing geographical disparities aid in enhancing the comprehension of hot springs for medical applications. This validates the application of hot spring medicine as a frontier trend and new hotspot in hot spring research.